Hubungan Trait Kepribadian dengan Self-Criticism pada Korban Kekerasan dalam Pacaran - Nazala Raditia; Suci Nugraha (Bandung Conference Series: Psychology Science, 2023)
Abstract. Dating relationships don't always go well for every couple. Violence can happen to every couple. Based on the results of the pre-survey conducted, the impact that occurs on victims of dating violence is that they continue to blame themselves, feel worthless so they do self-criticism because they have had a bad experience from their partner. Personality traits can determine the unique adjustment to the environment that influences individuals to be able or not to do self-criticism. This study aims to obtain the results of a study on the relationship between personality traits and self-criticism in victims of dating violence. This hypothesis is that there is a correlation between the big five personality trait and self-criticism in victims of dating violence. The researcher collected data using the FSCRS (The Forms of Selfcriticism / Self-Reassuring Scale) scale from Gilbert (2004) which was adapted by Nadia Altiany (2019) and the International Personal Item Pool – Big Five Model -25 (IPIP-BFM). -25) from Goldberg (1992) which has been adapted by Akhtar (2018). The results of this study indicate the relationship between extraversion and selfcriticism, r = 0.485, p = 0.000, agreeableness and self-criticism, r = 0.527, p = 0.000, conscientiousness and self-criticism, r = 0.702, p = 0.000, neuroticism with selfcriticism value r = 0.608 p value = 0.000, and openness to experience with selfcriticism value r = -0.205 p value = 0.053. This means that it shows a significant relationship between personality traits and self-criticism above with a fairly close category, only on the openness to experience trait which has a low category.Keywords: Trait, Self-Criticism, Dating Violence Abstrak. Hubungan pacaran tidak selalu berjalan dengan baik. Berdasarkan prasurvey yang dilakukan, dampak yang terjadi pada korban kekerasan dalam pacaran yaitu terus menyalahkan diri sendiri, merasa tidak berharga sehingga melakukan self-criticism karena memiliki pengalaman yang kurang baik dari pasangannya. Trait kepribadian dapat menentukan dalam penyesuaian diri secara unik terhadap lingkungan yang mempengaruh individu dapat atau tidak melakukan self-criticism. Penelitian ini bertujuan untuk memperoleh hasil kajian tentang hubungan trait kepribadian dengan self-criticism pada korban kekerasan dalam pacaran. Hipotesis ini adalah terdapat korelasi antara trait kepribadian big five personality dengan selfcriticism pada korban kekerasan dalam pacaran. Peneliti melakukan pengambilan data dengan menggunakan skala FSCRS (The Forms of Self-criticism /SelfReassuring Scale) dari Gilbert (2004) yang telah diadaptasi oleh Nadia Altiany (2019) dan International Personal Item Pool – Big Five Model -25 (IPIP-BFM-25) dari Goldberg (1992) yang telah diadaptasi oleh Akhtar (2018). Hasil penelitian ini menunjukkan hubungan antara extraversion dengan self-criticism nilai r=0.485 nilai p=0.000, agreeableness dengan self-criticism nilai r=0.527 nilai p=0.000, conscientiousness dengan self-criticism nilai r= 0.702 nilai p=0.000, neuroticism dengan self-criticism nilai r= 0.608 nilai p=0.000, dan openness to experience dengan self-criticism nilai r=-0.205 nilai p=0.053. Artinya menunjukkan hubungan yang signifikan antara trait kepribadian dengan self-criticism diatas dengan kategori cukup erat, hanya pada trait openness to experience yang memiliki kategori rendah.Kata Kunci: Trait Kepribadian, Kritik Diri, Kekerasan Dalam Pacaran